Japan in the Bluegrass - Karan, Pradyumna P. (Pradyumna Prasad) (The University Press of Kentucky, 2015)
Fifteen years after Toyota announced it would build a manufacturing plant in the heart of the Bluegrass, Kentucky crafts are being used to help sell Camrys at car dealerships in Japan and sushi and Japanese condiments are widely stocked on grocery shelves in a number of cities across Kentucky. In early 2000, the state boasted more than 100 Japanese companies representing a total investment of more than seven billion dollars, employing more than 33,000 Kentuckians. Japan in the Bluegrass is the first book to focus on the regional and local impact of the globalization of Japanese businesses, par.